The Diary of a Writer in Encuentro en Saint-Nazaire [Meeting in Saint-Nazaire] by Ricardo Piglia - Hernández Peñaloza, Amor Arelis (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In this article we study the genre of the intimate diary through the nouvelle Meeting in Saint- Nazaire (1988), which contains the “Diary of a Madman” by the fictional writer Stephen Stevensen. Used within the structure of the literary work, this fictional diary takes on a different meaning, because it renounces the communication of something intimate and secret, and instead becomes literature, “aesthetic communication”. This study also highlights the importance and magnitude of the journalistic genre in the narrative drive of an author like Ricardo Piglia. Additionally, this study of Encuentro en Saint-Nazaire [Meeting in Saint-Nazaire] will help show the characteristics of this type of pigliana prose, which functions as a laboratory of writing.